"Morir En Camino": Community Narratives about Childbirth Care in Rural Chiapas. Issue 3 (4th March 2019) - Amanuel, Hanna; Palazuelos, Daniel; Reyes, Andrea; Montaño, Mariana; Flores, Hugo; Molina, Rose L.
ABSTRACT: This anthropological study explores why more women in the rural Sierra Madre region of Chiapas, Mexico birth at home rather than at the hospital. Between January and May of 2014, the primary investigator conducted in-depth, semi-structured interviews with twenty-six interlocutors: six parteras (home birth attendants), nine pregnant women, four mothers, four healthcare providers, and three local government leaders. Participant observation occurred in the health clinic, participants' homes, and other spaces in a community with a population of 1, 188 people. Drawing from narrative analysis, the findings suggest that women face structural obstacles to accessing high-quality childbirth care, which lead them to give birth at home instead of the hospital. These obstacles include financial barriers in obtaining facility-based care and poor quality of care, such as mistreatment in the facility. The study highlights the importance of centreing community narratives in healthcare programming in order to bridge the implementation gap between women in rural communities, healthcare workers, and policymakers.